Stakeholders in support systems for self‐care for chronic illness: the gap between expectations and reality regarding their identity, roles and relationships. (27th May 2016) - Pumar‐Méndez, María J.; Mujika, Agurtzane; Regaira, Elena; Vassilev, Ivaylo; Portillo, Mari Carmen; Foss, Christina; Todorova, Elka; Roukova, Poli; Ruud Knutsen, Ingrid A.; Serrano, Manuel; Lionis, Christos; Wensing, Michel; et al.
Abstract: Background and objective: The spread of self‐care holds the promise of containing chronic illness burden. Falling within the framework of a FP7 collaborative research project, this paper reports the views of key informants from six countries regarding who the main stakeholders are at different levels in the support system for self‐care for patients with chronic illness (SSSC) and how they accomplish their role and collaborate. Methods: 90 Interviews with purposefully selected key informants from Bulgaria, Greece, the Netherlands, Norway, Spain and United Kingdom were conducted. Interviews involved government and local authorities, politicians, academics, health professionals and private sector representatives. Interviewers followed an expert opinion‐based guide. Analysis involved a cross‐country examination with thematic analysis and framework method techniques. Results: Key informants described the ideal SSSC as inclusive, interdependent and patient‐centred. The following main stakeholders in SSSC were identified: patients, governments, health‐care professionals, associations, private companies and the media. In the current SSSCs, collaboration among stakeholders within and across different levels was said to be lacking. Patients were seen as playing a passive subordinate role based on the following: their own attitudes; the paternalistic and medicalized attitudes of the health‐care professionals; their misrepresentation by patient associations; and their exposure to the damaging influences of media and industries. Conclusions: Making SSSC patient‐centred constitutes the greatest challenge for European authorities. Strategies must be revised for promoting patient participation. They should undergo changes so as to promote industry and media social responsibility and patient association advocacy capacity.